Autonomy, Capability, Subsidiarity as Key to a Social Ethics for Sustainability - Lynch, Kathleen (Trinity College Dublin. School of Religion. Discipline of Religions and Theology, 2019)
This thesis brings Amartya Sen'ss capability approach into dialogue with commitments in theological ethics to the autonomy and dignity of the human person in society, and to the integrity of creation. It applies the integrating framework of the autonomy approach in philosophical and theological ethics to the evaluation of approaches to sustainable development in social ethics. It first analyses long standing questions in ethics about human freedom and the problems of defending an environmental ethics whose starting point is in Kantian autonomy. It then reconnects this approach to a recent reformulation of the common good tradition, from which the principle of subsidiarity emerged (D. Hollenbach). It traces the development of the discourse of sustainability and the role agency plays in economic policy from Brundtland to capability theory, examining Sen's claim that poverty is better seen as 'capability failure' rather than merely low income. Sen advances a model of 'open impartiality' for mediating conflicts in social ethics but it needs the support of an anthropology that also defends 'mutuality', and this is secured through subsidiaric processes. The implications of analysing through a subsidiarity lens is that a social ethics of sustainability is better interpreted and operationalised not as 'open impartiality' but as 'intellectual solidarity' (Hollenbach) and a 'willingness to mutuality' (P. Ricoeur).
APPROVED
Keywords: Autonomy; Capability; Social ethics; Subsidiarity; Sustainability